The therapeutic effects of Rho-ROCK inhibitors on CNS disorders - Takekazu Kubo; Atsushi Yamaguchi; Nobuyoshi Iwata; Toshihide Yamashita (Dove Medical Press, 2008)
Takekazu Kubo1, Atsushi Yamaguchi1, Nobuyoshi Iwata2, Toshihide Yamashita1,31Department of Neurobiology, Graduate School of Medicine, Chiba University, 1-8-1 Inohana, Chuo-ku, Chiba 260-8670, Japan; 2Information Institute for Medical Research Ltd.; 3Department of Molecular Neuroscience, Graduate School of Medicine, Osaka University 2-2 Yamadaoka, Suita, Osaka 565-0871, JapanAbstract: Rho-kinase (ROCK) is a serine/threonine kinase and one of the major downstream effectors of the small GTPase Rho. The Rho-ROCK pathway is involved in many aspects of neuronal functions including neurite outgrowth and retraction. The Rho-ROCK pathway becomes an attractive target for the development of drugs for treating central nervous system (CNS) disorders, since it has been recently revealed that this pathway is closely related to the pathogenesis of several CNS disorders such as spinal cord injuries, stroke, and Alzheimer’s disease (AD). In the adult CNS, injured axons regenerate poorly due to the presence of myelin-associated axonal growth inhibitors such as myelin-associated glycoprotein (MAG), Nogo, oligodendrocyte-myelin glycoprotein (OMgp), and the recently identified repulsive guidance molecule (RGM). The effects of these inhibitors are reversed by blockade of the Rho-ROCK pathway in vitro, and the inhibition of this pathway promotes axonal regeneration and functional recovery in the injured CNS in vivo. In addition, the therapeutic effects of the Rho-ROCK inhibitors have been demonstrated in animal models of stroke. In this review, we summarize the involvement of the Rho-ROCK pathway in CNS disorders such as spinal cord injuries, stroke, and AD and also discuss the potential of Rho-ROCK inhibitors in the treatment of human CNS disorders.Keywords: neuron, Rho, Rho-kinase, axonal regeneration, central nervous system disorder